2021
DOI: 10.1186/s12888-021-03626-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring COVID-19 patients’ experiences of psychological distress during the disease course: a qualitative study

Abstract: Background The Coronavirus Disease 2019 (COVID-19) is an emerging disease with many unknown clinical and therapeutic dimensions. Patients with COVID-19 experience a variety of psychological problems during the disease. Understanding patients’ mental condition and their distress during the disease is the first step to help these patients. So, the aim of this study was to explain COVID-19 patients’ experiences of psychological distress during the disease course. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Across the globe, people infected with or recovered from SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus-2) became a target of ostracism, humiliation, harassment and even violence. Studies from Pakistan, Uganda, Malaysia, India, China, Ghana, Iran and Brazil found that COVID-19 survivors and even their families were often rejected from social life or essential services and felt humiliated 12–21. COVID-19 survivors were blamed for the disease13 15 16 and perceived as a source of infection even after being cured,12 16 21 22 some reported finical hardship as a consequence 13 19 23.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across the globe, people infected with or recovered from SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus-2) became a target of ostracism, humiliation, harassment and even violence. Studies from Pakistan, Uganda, Malaysia, India, China, Ghana, Iran and Brazil found that COVID-19 survivors and even their families were often rejected from social life or essential services and felt humiliated 12–21. COVID-19 survivors were blamed for the disease13 15 16 and perceived as a source of infection even after being cured,12 16 21 22 some reported finical hardship as a consequence 13 19 23.…”
Section: Introductionmentioning
confidence: 99%
“…Stereotyping was common,15 especially blaming the poor, labourers and migrants16 or people of seemingly Asian origin 24–26. Research from Malaysia, Iran and Tunisia found that affected people made efforts to hide the infection 15 20 27. Due to stigma, people with suspected COVID-19 might avoid testing or treatment facilities, leading to poor health outcomes and the further spread of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…Feelings of anxiety were also highly endorsed by COVID-19 patients in similar qualitative studies in Iran and South Korea. 27 , 36 Uncertainty , the second-most commonly coded theme in our study, was also a prominent concept in a qualitative study on a COVID-19 recovery cohort of twenty-four subjects by Santiago-Rodriguez and colleagues. 24 Relatedly, in our study, individuals reported hypervigilance about their symptoms and not knowing exactly how to interpret their seriousness or significance.…”
Section: Discussionmentioning
confidence: 67%
“…Patients with COVID-19 experience great psychological distress during the acute phase of the disease or even long after recovery. [20]. Other study showed that patients with COVID-19 would experience a di cult time during isolation due to physical problems, loneliness, being separated from the family [21].…”
Section: Discussionmentioning
confidence: 99%